2015
DOI: 10.1038/mp.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting suicidality using a combined genomic and clinical risk assessment approach

Abstract: Worldwide, one person dies every 40 seconds by suicide, a potentially preventable tragedy. A limiting step in our ability to intervene is the lack of objective, reliable predictors. We have previously provided proof of principle for the use of blood gene expression biomarkers to predict future hospitalizations due to suicidality, in male bipolar disorder participants. We now generalize the discovery, prioritization, validation, and testing of such markers across major psychiatric disorders (bipolar disorder, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
165
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 42 publications
9
165
0
Order By: Relevance
“…This study was the first to examine relationships between SKA2 and suicidal behavior in a military cohort and, consistent with research in civilian samples, [6-8] found that variation at the SKA2 locus identified in previous research (CpG locus cg13989295) was associated with suicidal thoughts and behaviors. The specificity of the SKA2 association with current, but not lifetime, suicide phenotypes suggests methylation at this locus may index dynamic processes related to ongoing suicidal behavior and speaks to its potential utility for measuring suicide risk.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This study was the first to examine relationships between SKA2 and suicidal behavior in a military cohort and, consistent with research in civilian samples, [6-8] found that variation at the SKA2 locus identified in previous research (CpG locus cg13989295) was associated with suicidal thoughts and behaviors. The specificity of the SKA2 association with current, but not lifetime, suicide phenotypes suggests methylation at this locus may index dynamic processes related to ongoing suicidal behavior and speaks to its potential utility for measuring suicide risk.…”
Section: Discussionsupporting
confidence: 74%
“…In two subsequent studies, Niculescu and colleagues found decreased SKA2 expression levels in blood in suicide decedents compared to controls [7] and SKA2 expression levels prospectively predicted suicidal ideation in psychiatric patients. [8] …”
Section: Introductionmentioning
confidence: 99%
“…Notably, some studies demonstrate that state level stress can be influenced by trait level anxiety [10]. Model predictive accuracies vary between ~70 and 85 % in various cohorts and are consistent with SKA2 gene expression-based prediction accuracies reported by other groups [8, 11]. The statistical interaction with stress is likely related to the physiological role SKA2 plays in mediating HPA axis activity.…”
Section: Introductionsupporting
confidence: 67%
“…This attention to risk factors has extended to genetic and other biological factors [Oquendo et al 2016; Sudol and Mann 2017; Turecki 2014], with the goal of developing a bio-signature for suicide [Oquendo et al 2014]. Recent reports of a combined genetic-epigenetic risk marker for suicidality in SKA2 [Guintivano et al 2014; Kaminsky et al 2015] are of considerable interest, and await further replication in population-based samples, as do other multivariate approaches that incorporate genomic and clinical risk factors [Niculescu et al 2015b]. Although twin studies have documented genetic influences on suicide-related phenotypes (heritability ~30% – 55%) [Tidemalm et al 2011], it is clear that suicidality is a multi-determined, genetically complex trait, as is the case for virtually all mental and behavioral disorders [Gelernter 2015].…”
Section: Introductionmentioning
confidence: 99%